Introductory statistics - Mann, Prem S. (Wiley, 2011)
* Introductory Statistics has made statistics both interesting and accessible to a wide and varied audience. * The explanation of statistical methods and concepts is clear and concise. * The text contains a wealth of examples that are well-sequenced and thorough, displaying all facets of concepts.